2013
DOI: 10.7314/apjcp.2013.14.9.5519
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus in Male and Female Urine by Electrochemical DNA Chip and PCR Sequencing

Abstract: Background: Cervical cancer is the second most common cancer in Thai women after breast cancer. Currently, the Papanicolaou (Pap) smear is the recommended procedure for cervical cancer screening in Thailand, but only a relatively small percentage of women follow this screening program. An alternative method to detect HPV genotypes associated with cervical cancer is self-sampling of urine, which is a more widely accepted method. Our study aimed to evaluate the prevalence of HPV in Thai women using urine and cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…When cervical testing for HPV is required, these results suggest that urine sample collection provides an alternative non-invasive sampling method for monitoring HPV infection in women. In a previous study, the overall percentage agreement between HPV detection in urine and cervical samples was 88% using the Cobas 4800 HPV test (Bernal et al, 2014), 75% using an electrochemical DNA chip (Nilyanimit et al, 2013) and, in this study, the percentage was 65.2%. The undeniable advantage in testing urine sample is its acceptance and convenience for the patients, although better results are obtained with first urine in the morning (Vorsters et al, 2014).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…When cervical testing for HPV is required, these results suggest that urine sample collection provides an alternative non-invasive sampling method for monitoring HPV infection in women. In a previous study, the overall percentage agreement between HPV detection in urine and cervical samples was 88% using the Cobas 4800 HPV test (Bernal et al, 2014), 75% using an electrochemical DNA chip (Nilyanimit et al, 2013) and, in this study, the percentage was 65.2%. The undeniable advantage in testing urine sample is its acceptance and convenience for the patients, although better results are obtained with first urine in the morning (Vorsters et al, 2014).…”
Section: Discussionsupporting
confidence: 55%
“…HPV DNA urine testing can be used to identify abnormal cells in adolescent girls and young women who do not wish to have a vaginal examination (Vorsters et al, 2014; Enerly, Olofsson & Nygård, 2013). Some studies have reported a high HPV detection sensitivity for urine-based assays (Forslund et al, 1993; Hagihara et al, 2016; Bernal et al, 2014), while other studies have reported a low HPV detection sensitivity from urine-based assays (D’Hauwers et al, 2007; Nilyanimit et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The overall concordance percentage reported in the present study was in accordance with the study carried out in Thailand (Nilyanimit et al, 2017). There are reports of good agreement of HPV DNA detection in paired urine and cervical samples (Tanzi et al, 2013;Sahasrabuddhe et al, 2014;Stanczuk et al, 2003;Nicolau et al, 2014;Nilyanimit et al, 2013;Bernal et al, 2014). Another study carried out among thirty cervical cancer cases, urine samples of 28 cases were HPV DNA positive, while all the thirty cervical samples were tested predictive value of HPV detection in urine samples was 96.4% and negative predictive value 39%.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the cost of testing may discourage patients from choosing to screen for HPV (Oranratanaphan et al, 2014). To improve screening coverage, self-administered sample collection could be an alternative to Pap smear test (Nilyanimit et al, 2013;Scarinci et al, 2013). Previous studies examined the sensitivity and predictive value of HPV detection by comparing self-collected and physician-collected samples for HPV screening.…”
Section: Introductionmentioning
confidence: 99%